Balancing constitutional rights and institutional identity: Evidence from Muhammadiyah Universities in Eastern Indonesia - Syamsul Arifin; Le Xuan Tung; Nur Kafid; Ahmad Zainul Hamdi; Khoirun Niam (Faculty of Law, University of Muhammadiyah Malang, 2025)
This study examines the relationship between constitutional rights and institutional religious identity through Islamic Religious Education (IRE) at Muhammadiyah universities in Eastern Indonesia, in which the majority of students are Christian. Although the law guarantees students’ rights to receive religious education in accordance with their beliefs, some Islamic higher education institutions pay insufficient attention to this provision. Through interviews, document analysis, and classroom observations, this study investigates how religious education at Muhammadiyah universities is managed to balance Muhammadiyah’s institutional educational identity with the legal requirements related to students’ constitutional rights to obtain religious education that corresponds to their respective religions. The findings show Muhammadiyah’s commitment to providing religious education that accommodates students' religious diversity through an instructional approach known as Multicultural AIK. Nevertheless, more inclusive steps remain necessary, including facilitating religious education that explicitly indicates that the instruction students receive aligns with the religion they adhere to.